Speech Act Realization on Handbook Mitigation Disaster in Japan - Radhiya, Rd. Januar; Martawijaya, Asteria Permata (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2020)
This study investigates speech act strategies used in earthquake mitigation handbooks in Japan, and focuses on finding the type of communicative functions of the speech act strategies used. The government of Japan has provided online and printed handbooks for the people, to reduce risks to a minimum level regarding the disaster so people can prepare beforehand. The data in this study were collected from online leaflet and handbook regarding earthquake mitigation provided by 9 government city’s websites, the Ministry of Foreign Affairs of Japan, and by collecting actual handbook and leaflets from Indonesian lives in Japan. The data were analysed using descriptive qualitative method. Collected data then categorized into assertive and directive speech acts, negative and positive politeness based on Brown and Levinson’s politeness theory, and focusing on expression of consideration (hairyo hyougen). This study found that there are 659 statements related to earthquake disaster mitigation collected from the data. Also, the findings showed that there are 179 assertive and 480 directives speech acts, with more of imperative directive speech than prohibition directive speech. Moreover, Japanese government tend to use hairyou hyougen on their leaflet and handbook disaster mitigation to show respect to the reader.